The 2020s-The Download on Computer Literacy in 1984 with Dr. Jeri Wieringa. (15th June 2022) - Welch, Emma
Abstract : Beginning in 2020, the Bulletin feature known as The Download has been readers' guide to the increasingly digital study of religion. For this issue, editorial assistant Emma Welch sat down with The Download's Jeri Wieringa to discuss Robert A. Kraft's "In Quest of Computer Literacy" and the legacy of the Bulletin series, Offline. Wieringa remarks on how the concept of computer literacy has evolved as a result of technological advancements and notes the subsequent challenges present in this new digital age.